2017
DOI: 10.1007/s00018-017-2452-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of neuropeptides in adverse myocardial remodeling and heart failure

Abstract: In addition to traditional neurotransmitters of the sympathetic and parasympathetic nervous systems, the heart also contains numerous neuropeptides. These neuropeptides not only modulate the effects of neurotransmitters, but also have independent effects on cardiac function. While in most cases the physiological actions of these neuropeptides are well defined, their contributions to cardiac pathology are less appreciated. Some neuropeptides are cardioprotective, some promote adverse cardiac remodeling and hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 215 publications
(290 reference statements)
0
13
0
Order By: Relevance
“…It has been postulated that these differences may be due to high NPY levels only occurring when there is sustained and sufficiently high sympathetic activation (Pedrazzini et al, 2003 ). As recently discussed (Widiapradja et al, 2017 ), it should be noted that there may also be differences between the plasma levels of NPY measured in these studies, and actual cardiac tissue concentrations. A high cardiac output model of heart failure in the rat found high plasma levels but reduced tissue levels in the heart (Callanan et al, 2007 ) although this may be as a result of increased cardiac release of NPY.…”
Section: Neuropeptide Y As An Important Mediator Of Cardiovascular DImentioning
confidence: 74%
“…It has been postulated that these differences may be due to high NPY levels only occurring when there is sustained and sufficiently high sympathetic activation (Pedrazzini et al, 2003 ). As recently discussed (Widiapradja et al, 2017 ), it should be noted that there may also be differences between the plasma levels of NPY measured in these studies, and actual cardiac tissue concentrations. A high cardiac output model of heart failure in the rat found high plasma levels but reduced tissue levels in the heart (Callanan et al, 2007 ) although this may be as a result of increased cardiac release of NPY.…”
Section: Neuropeptide Y As An Important Mediator Of Cardiovascular DImentioning
confidence: 74%
“…Given the role of SP in cardiovascular disease (Dehlin and Levick, 2014;Widiapradja et al, 2017), we were interested in whether cardiac MCs from diseased hearts were more responsive to SP. Accordingly, we isolated MCs from SHR hearts and compared SP-induced histamine release with SD normotensive MCs.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropeptides, including SP, are being increasingly recognized as important factors in the development of adverse cardiac remodelling and heart failure (D'Souza et al, 2007;Dehlin and Levick, 2014;Mak et al, 2011;Mak et al, 2015;Morrey et al, 2010;Ng et al, 2014;Robinson et al, 2009;Robinson et al, 2016;Weglicki et al, 1994;Widiapradja et al, 2017), and MCs are also important in the development of numerous cardiac pathologies (Batlle et al, 2007;Brower et al, 2002;Brower and Janicki, 2005;Frangogiannis et al, 1998;Levick et al, 2009;Marone et al, 1995;McLarty et al, 2011;Olivetti et al, 1989;Stewart et al, 2003). Therefore, it is important to better understand neuropeptide interactions with cardiac MCs.…”
Section: Introductionmentioning
confidence: 99%
“…As to cluster 8, we noted that a few genes were uniquely expressed with varied functions. These include Apoe, Tgfbi ; Wif1 , which modulates cardiomyocyte differentiation 46 necessary for cardiac remodeling in myocardial infarction and also promotes DCM 47 ; Clu , myocardial injury marker 48 ; and Npy, which has a role in cardiac remodeling and heart failure 49 . These data indicated that clusters 5, 6, and 8 were mainly involved in the cardiac remodeling process in myocarditis.…”
Section: Resultsmentioning
confidence: 99%